The role of enriched environment in neural development and repair - Han, Yu; Yuan, Mei; Guo, Yi-Sha; Shen, Xin-Ya; Gao, Zhen-Kun; Bi, Xia (Frontiers in Cellular Neuroscience, 2022)
In addition to genetic information, environmental factors play an important role in the structure and function of nervous system and the occurrence and development of some nervous system diseases. Enriched environment(EE) can not only promote normal neural development through enhancing neuroplasticity but also play a nerve repair role in restoring functional activities during CNS injury by morphological and cellular and molecular adaptations in the brain. Different stages of development after birth respond to the environment to varying degrees. Therefore, we systematically review the pro-developmental and anti-stress value of EE during pregnancy, pre-weaning, and “adolescence” and analyze the difference in the effects of EE and its sub-components, especially with physical exercise. In our exploration of potential mechanisms that promote neurodevelopment, we have found that not all sub-components exert maximum value throughout the developmental phase, such as animals that do not respond to physical activity before weaning, and that EE is not superior to its sub-components in all respects. EE affects the developing and adult brain， resulting in some neuroplastic changes in the microscopic and macroscopic anatomy, finally contributing to enhanced learning and memory capacity. These positive promoting influences are particularly prominent regarding neural repair after neurobiological disorders. Taking cerebral ischemia as an example, we analyzed the molecular mediators of EE promoting repair from various dimensions. We found that EE does not always lead to positive effects on nerve repair, such as infarct size. In view of the classic issues such as standardization and relativity of EE have been thoroughly discussed, we finally focus on analyzing the essentiality of the time window of EE action and clinical translation in order to devote to the future research direction of EE and rapid and reasonable clinical application.